Unpacking the ‘black box’ of public expenditure data in Africa: Quantification of agricultural spending using Mozambique’s budget reports - Mogues, Tewodaj; Caceres, Leonardo (Ubiquity Press, Ltd., 2018)
This paper undertakes a detailed examination of the availability and quality of data on public expenditures in agriculture in Africa. We consider the case of Mozambique, a country characterised by low income and low administrative capacity, but also by a policy environment that has turned a focused lens on public funding to agriculture. We explore the extent to which domestic analysts may be able to access and use such data to reliably quantify public resource allocation to the sector, and to unpack the ‘black box’ of what goes into country-level public expenditure statistics.